DINAMIKA ANCAMAN DAN RESPON PERTAHANAN DI LAUT NATUNA UTARA: STUDI KUALITATIF STRATEGI TNI AL DALAM MENJAGA ZONA PERBATASAN - Elisabeth Tanti; Muhammad Zulkifli; Basuki Tri Usodo; Hendrik Kurniawan; Wahyu Sasono (UNIMAR AMNI Semarang, 2026)
Abstract. The North Natuna Sea is often the site of various threats to Indonesia's maritime sovereignty, including territorial violations by foreign vessels, illegal fishing, and unauthorized survey and exploration activities. These threats require a rapid, precise, and coordinated defense response to maintain regional stability. The Indonesian Navy (TNI AL) implements an adaptive defense strategy, utilizing routine patrols using warships and reconnaissance aircraft, technology-based surveillance such as radar and Vessel Monitoring System (VMS), and inter-agency coordination. This approach ensures that any incidents of violations can be detected early and responded to effectively. Qualitative analysis shows that the effectiveness of the TNI AL's defense depends on personnel readiness, strategic planning, and the involvement of coastal communities. The physical presence of the TNI AL in the waters, combined with scheduled patrols and rapid response, has a preventive effect on illegal activities. In addition, coordination with relevant agencies and the use of technology strengthen threat detection and mitigation capabilities, thereby maintaining the security of the border zone. The results of the study confirm that a holistic and responsive defense strategy is a key factor in maintaining the security and sovereignty of the North Natuna Sea. Adapting to the dynamics of threats and strengthening coordination between units enables the Indonesian Navy to maintain an effective presence, while also In addition, coordination with relevant agencies and the use of technology strengthen threat detection and mitigation capabilities, thereby maintaining security in the border zone. The results of the study confirm that a holistic and responsive defense strategy is a key factor in maintaining the security and sovereignty of the North Natuna Sea. Adapting to the dynamics of threats and strengthening coordination between units enables the Indonesian Navy to maintain an effective presence, while minimizing potential risks that could harm Indonesia. Keywords: North Natuna Sea, Maritime Security, Threats Defense Strategy, Indonesian Navy, Indonesian Border Zone